2010
DOI: 10.1007/s10750-010-0289-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of the HKHbios: a new biotic score to assess the river quality in the Hindu Kush-Himalaya

Abstract: Within the ASSESS-HKH project (Development of an Assessment System to Evaluate the Ecological Status of Rivers in the Hindu KushHimalayan (HKH) region-a research project funded by the European Union; contract number: INCO-CT-2005-003659) a benthic invertebrate-based scoring system (HKHbios; Hindu Kush-Himalayan biotic score) was developed. The development was based on multi-habitat samples from 198 sampling sites located in five ecoregions and five Asian countries (Bangladesh, Bhutan, India, Nepal and Pakistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Its assemblages are also considered as surrogates for the insect community structure in water bodies, being capable of indicating changes in the biological integrity of these ecosystems (Silva et al 2010). This can be proven from the newly developed HKHbios scoring (Ofenböck et al 2010) list for the Hindu Kush Himalayan river system (Fig. 2).…”
Section: Introductionmentioning
confidence: 91%
“…Its assemblages are also considered as surrogates for the insect community structure in water bodies, being capable of indicating changes in the biological integrity of these ecosystems (Silva et al 2010). This can be proven from the newly developed HKHbios scoring (Ofenböck et al 2010) list for the Hindu Kush Himalayan river system (Fig. 2).…”
Section: Introductionmentioning
confidence: 91%
“…A number of macroinvertebrate-based score systems have been developed in Nepal also (Sharma, 1996;Nesemann, 2009;Ofenböck et al, 2010) and have been used in a number of bioassessment studies of streams (Sharma et al, 2005;Gurung et al, 2016). These organisms have provided consistent results with corresponding stressors present in the water bodies proving these organisms as effective bioindicators of aquatic health.…”
Section: Discussionmentioning
confidence: 99%
“…Data indicated that the health of the streams had no differences between seasons. The HKH biotic score (Ofenböck et al 2010), indicated that water quality values were similar across all streams. Here the organisms are assigned a tolerance number from 1-10 pertaining to that group's known sensitivity to organic Mean pH was slightly alkaline, during the postmonsoon (7.20 ± 0.33) and pre-monsoon (7.19 ± 0.42).…”
Section: D) Diversity Evenness and Richness Among The Streamsmentioning
confidence: 99%